A social identity perspective of social media's impact on satisfaction with life. Issue 6 (28th January 2020) - Dutot, Vincent
Abstract: Social media platforms have become an (almost) obligatory part of our lives and activities. However, many disadvantages have emerged such as an increase in dependency on social media owing to addictions known as the dark side of social media. The current research seeks to understand the impact of specific aspects of this dark side, viz. social media addiction, fear of missing out, and narcissism, on self‐esteem, and their links with an individual's satisfaction with life (SwL). The results of a quantitative survey ( n = 260) show the salient impact of these aspects on self‐esteem as well as the preponderant role of collective self‐esteem in SwL. Academic and managerial implications are discussed.